The Fate of Carbon and Nutrients Exported Out of the Southern Ocean. Issue 10 (26th October 2018) - Hauck, Judith; Lenton, Andrew; Langlais, Clothilde; Matear, Richard
Abstract : Southern Ocean (SO) nutrient export via mode and intermediate waters is known to affect global biological production. The accompanying effects on the CO2 flux outside the SO are less certain. We performed idealized model simulations to separate the transient effects of SO carbon pumps on nutrients, primary production, and CO2 flux outside the SO. The SO biological carbon pump leads to dissolved inorganic carbon and nutrient reduction at the surface and in the exported water masses, and to a dissolved inorganic carbon increase at depth through the sinking of organic matter. When primary production is suppressed in the SO, only 30% of SO export, 43% of SO net primary production, and 50% of biologically driven SO CO2 flux are compensated outside the SO on a 200‐year time scale. In contrast, when the abiotically driven CO2 flux is suppressed, 90% of CO2 outgassing in the SO is compensated by air‐sea CO2 exchange outside the SO. The longer sequestration time scale of the biological carbon pump can be explained by incomplete compensation of primary production. This is a result of almost complete compensation of diatom productivity and no compensation of nanophytoplankton productivity due to feedbacks in phytoplankton community composition. The longer sequestration time scale is further sustained by the sinking and remineralization of particles in the deep ocean that are not in contact with the atmosphere over the 200‐year time scale considered. As SO biologically driven CO2 flux is only partly compensated outside the SO, potential future changes in SO productivity may have an important impact on the global carbon cycle. Key Point: The Southern Ocean biological carbon pump has longer sequestration time scale than physical pump